2009
DOI: 10.1002/pros.20991
|View full text |Cite
|
Sign up to set email alerts
|

Expression of multidrug resistance proteins in prostate cancer is related with cell sensitivity to chemotherapeutic drugs

Abstract: Low chemotherapy response observed in PC primary cultures could be explained, in part, by the high levels of MDR proteins (intrinsic MDR phenotype), and also, by their over-expression induced after long-term exposure to drugs (acquired MDR phenotype), which increase treatment resistance. Prostate 69: 1448-1459, 2009. (c) 2009 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 32 publications
1
76
0
1
Order By: Relevance
“…64 On the other hand, BRCP was shown to be expressed in both cell lines, while MRP-2 was only found in PC3 cells. 65,66 One possible explanation for the increased cytotoxicity following the combination treatment, despite the redundancy of the proteins targeted, is that the small TKIs are also known inhibitors of these efflux pumps.…”
mentioning
confidence: 94%
“…64 On the other hand, BRCP was shown to be expressed in both cell lines, while MRP-2 was only found in PC3 cells. 65,66 One possible explanation for the increased cytotoxicity following the combination treatment, despite the redundancy of the proteins targeted, is that the small TKIs are also known inhibitors of these efflux pumps.…”
mentioning
confidence: 94%
“…Chemoresistant PC3 cells do not overexpress P-gp, whereas resistant DU145 cells exhibit both overexpression of the protein and restored chemo-sensitivity with P-gp inhibition (Makarovskiy et al 2002, Takeda et al 2007. Furthermore, exposure to mitoxantrone and docetaxel results in increased multidrug-resistant protein expression in chemo-sensitive prostate cancer cell lines (Sanchez et al 2009). Although MDR1 is well understood, MRP1 is also emerging as an important element in prostate cancer chemoresistance (Zalcberg et al 2000.…”
Section: Multidrug Resistance Proteinsmentioning
confidence: 99%
“…Previous studies have demonstrated that MDR1 is an important candidate gene in the pathogenesis of osteoporosis (van Brussel and Mickisch, 2003;Sanchez et al, 2009;Sanchez et al, 2011). To the best of our knowledge, the current study is the first to investigate the prevalence of the c.1465C>T variant, which is located in exon14 of MDR1, and evaluate its relationship with Pca risk.…”
Section: Discussionmentioning
confidence: 87%
“…The pathogenesis of Pca is still largely unknown, with genetic and environmental factors likely contributing to increased risk of the disease (Pienta and Esper 1993;Lichtenstein et al, 2000;Schaid, 2004). Several candidate genes have been suggested to be associated with Pca, including multidrug resistance 1 (MDR1) (van Brussel and Mickisch, 2003;Sanchez et al, 2009;Sanchez et al, 2011), X-ray repair complementing group 1 (Hirata et al, 2007;Agalliu et al, 2010;Dhillon et al, 2011;Kuasne et al, 2011;Langsenlehner et al, 2011), xeroderma pigmentosum group D gene (Mandal et al, 2010), APEX nuclease 1 gene (Agalliu et al, 2010;Kuasne et al, 2011;Mittal et al, 2012), Toll-like receptor 4 (Jing et al, 2012), axis inhibition protein 2 (Pinarbasi et al, 2011), 2-5A-dependent RNase (Wei et al, 2012), complementation group G gene (Berhane et al, 2012), and N-acetyltransferase types 1 (Gong et al, 2011) and 2 (Gong et al, 2011;de Lima Junior et al, 2012). MDR1 is an important candidate gene for Pca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation